Natural feed resources and their availability patterns - Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1984)
Discusses natural feed resources and their availability patterns in Nigeria. Lists grassland, communities and their yield under natural environment and, common browse species and their nutritive value in Bin-Yauri Grazing Reserve in the late dry season.